Penciptaan Nilai Perusahaan: Spesial Isu Merger dan Akuisisi Perusahaan Publik di Indonesia - Perwito, Perwito; Wibowo, Lili Adi; Hamdani, Dadan (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2020)
Creating corporate value is the company's main goal, making various strategic decisions continuously sothat it has a positive impact on the company and its esteem on the prosperity of shareholders. This studyaims to analyze the Creation of Company Value through Mergers and Acquisitions.This study uses a quantitative descriptive verification approach, the object of research in public sectorbanking companies in Indonesia. To know the difference in the value of the company before and after M &A by using Paired sample T test.The results showed that the asset restructuring strategy through Mergers and Acquisitions did not have apositive and significant impact on corporate value creation. This shows the absence of corporate financialsynergy through mergers and acquisitions. Further research related to asset restructuring throughcorporate actions; Initial Public Offering (IPO), right issue, Leverage Buy-out..